An experimental evaluation of polyamide membrane-silica nanoparticles for the concentration of pomegranate juice. (February 2023) - Li, Xiang; Liu, Fangfang; Abdollahpour, A.; Jazebizadeh, M.H.; Wang, Jialian; Semiromi, D.
Abstract: Membrane processes are used in the food and nutrient industry in terms of their proper performance and selective separation. Using the membranes in fruit juice concentrating operations improves its quality via shelf-life increases. The advantage of reverse osmosis (RO) and membrane technology over other methods is its non-chemical reaction to fruit juice which increases the concentration of fruit juice. The membranes were made of three layers of non-woven polyester layer for the mechanical strength of the membrane, polyester sulfone polymer with polyamide consisting of polymerization of M-Phenylenediamine (MPD) and benzene tricarbonyl chloride. Trimethyl chloride (TMC) was used to modify the properties of the membrane in the second layer using silica nanoparticles. The feed was sugar-free pomegranate juice added by SUNICH Company with an initial Brix value of 14.9% and an input feed of 6.6% to the RO system. The DESIGN-EXPERT method for the design of experiments (DOE) by considering three parameters of weight percentage of polyester sulfone polymer (12, 16, and 20%), silica nanoparticles (0, 0.1, and 0.2 wt%), and operating pressure were used (20, 25, and 30 times). Under optimal conditions, 46.15% of the concentrated pomegranate juice were obtained by experiment and the amount of brix increased from 33.24% to 47.21%. Scanning electron microscope (SEM), Fourier-transform infrared spectroscopy (FTIR), and contact angle tests for membranes were used. In the analysis of contact angle by examining the degree of hydrophilicity and contact angle of water droplets, it was found that the presence of silica nanoparticles and polyamide layer caused more hydrophilicity of membranes. It can be concluded that the pressure parameter, together with the presence of nanoparticles and polymer percentages, contribute to the most successful procedure of concentrating pomegranate juice. Graphical abstract: Image 1